Alternatives for Valorization of Agricultural Resources of Low Commercial Value in Benin: Production of First Generation's Bioethanol: A Review - GBOHAIDA, Virginie; AGBANGNAN, DOSSA COKOU PASCAL; BOTHON, FIFA THEOMAINE DIANE; AVLESSI, FÉLICIEN; WOTTO, VALENTIN DIEUDONNÉ; SOHOUNHLOUE, KOKO CODJO DOMINIQUE (My University, 2018)
Currently, the possibilities for energetic valorization of the biomass by biotechnological processes represent a solution of choice for the use of low trading value agricultural products, waste from food industries, crop residues, etc. The valorization of this biomass, especially of organic nature, is realized through various biotechnological processes such as bioconversion into ethanol. The present study is a literature review that aims to encourage the recovery of agro-industrial waste and reducing post-harvest losses through the evaluation of bioethanol fuel production possibilities by using sugar commodities (pineapple peelings, mango, cashew apple) and local starch (cassava, sorghum). The realization of this study is an important challenge in environmental domain and on socio-economic level through employment creation, socio-economic integration of women, and the creation of added value to peasants..
Keywords: biomass; energetic valorization; biotechnological processes; bioethanol fuel